Preventive Effects of Alprostadil Against Contrast-Induced Nephropathy Inpatients With Renal Insufficiency Undergoing Percutaneous Coronary Intervention. (May 2018) - Yang, Shi-Cheng; Fu, Nai-Kuan; Zhang, Jing; Liang, Min; Cong, Hong-Liang; Lin, Wen-Hua; Tian, Feng-Shi; Lu, Cheng-Zhi; Sun, Ting-Ting; Zhang, Wen-Ya; Ma, Zhen-Hua
We investigated the preventive effect of alprostadil on contrast-induced nephropathy (CIN) in patients with renal insufficiency undergoing percutaneous coronary intervention (PCI). A total of 300 patients with creatinine clearance (crCl) ≤60 mL/min undergoing PCI were randomly assigned to alprostadil or a control group. The primary end point was the incidence of CIN defined as an increase in serum creatinine (Scr) levels by ≥0.5 mg/dL or≥ 25% after administration of the contrast media within 72 hours. The secondary end points were (1) changes in Scr and crCl within 72 hours and (2) the incidence of major adverse events during hospitalization. The incidence of CIN was 2.7% (4/150) in the alprostadil group, and 8.7% (13/150) in the control group (χ 2 = 5.05, P = .043).There was no difference regarding the incidence of major adverse events during hospitalization between the alprostadil group and control groups (2.7% vs 4.0%, P = .750). Multivariate logistic regression analysis showed that alprostadil was an independent protective factor for CIN (odds ratio = 0.136, 95% confidence interval: 0.020-0.944, P = .044). Prophylactic administration of alprostadil may prevent CIN in patients with renal insufficiency undergoing PCI.